Purification and functional characterization of protoplasts and intact vacuoles from grape cells - Gerós Hernâni; Lecourieux Fatma; Vignault Céline; Silva Rui; Fontes Natacha; Delrot Serge (BMC Research Notes, 2010)
Abstract Background During grape berry ripening, the vacuoles accumulate water, sugars and secondary metabolites, causing great impact in plant productivity and wine quality. However, the molecular basis of these compartmentation processes is still poorly understood. As in many species, the major bottleneck to study these aspects in grapevine is to obtain highly purified vacuoles with a good yield. The present paper describes an isolation method of protoplasts and intact vacuoles from grape berry cells and their functional characterization by transport and cytometric assays. Findings Protoplasts were prepared by enzymatic digestion of grape cells, and vacuoles were released and purified by a Ficoll step gradient centrifugation. The tonoplast stained strongly with the fluorescent dye FM1-43 and most vacuoles maintained an internal acidic pH, as assessed by Neutral Red. Flow cytometry analysis of vacuole samples incubated with the calcium-sensitive fluorescent probe Fluo-4 AM revealed a well-defined sub-population of intact vacuoles. As assessed by the pH-sensitive probe ACMA, intact vacuoles generated and maintained a pH gradient through the activity of V-ATPase and V-PPase and were able to transport Ca2+ via a proton-dependent transport system. Conclusions Highly pure, intact and functional protoplast and vacuole populations from grape cells were obtained with the present method, which revealed to be fast and efficient. The capacity of the vacuole population to sequester protons and accumulate Ca2+ strongly suggests the intactness and physiological integrity of these extremely fragile organelles. Grapevine protoplasts and vacuoles may be used as models for both basic research and biotechnological approaches, such as proteomics, solute uptake and compartmentation, toxicological assessments and breeding programs.